Ladoga Ringed Seal (Pusa hispida ladogensis) Can Breed on Land: A Case Study of the Nursing Period - Loseva, Anna; Chirkova, Olga; Akhatov, Evgeniy (The Arctic Institute of North America, 2022)
The ringed seal gives birth and nurses offspring in a subnivean lair in fast ice. Its breeding habitat is transforming under the impact of climate change. Here we report the outcome of an observation of a female freshwater Ladoga ringed seal (Pusa hispida ladogensis) and her pup during the 2020 breeding season, when less than 1% of Lake Ladoga was covered with ice. We located a newborn pup in a coastal zone of an island and tracked its survival on land using the camera trap method during daylight. Altogether, we captured 2978 photos, in which the seals were present in 637. The female nursed the pup at the birth site for 34 – 37 days, which is similar to the lactation period in lairs of the Arctic subspecies (36 – 41 days, 39 days on average). The female either stayed with the pup or spent time in prolonged aquatic bouts during the day. Percentage of suckling was in the range of 2.4% – 4.7% (mean 3.3%, SD = 1.1) on different days. Based on an additional video recording, we found that the pup’s behaviour was characterized by a high level of vigilance in comparison with openly breeding phocid seals. This case study indicates that the ringed seal in Lake Ladoga is able to nurse pups on land from soon after birth to pre-weaning. However, breeding success in warm springs can be constrained by predator pressure. Le phoque annelé donne naissance à ses petits et les nourrit dans un abri subnival de la glace rapide. Son habitat de reproduction se transforme sous l’effet du changement climatique. Ici, nous présentons le résultat de l’observation d’un phoque annelé de Ladoga (Pusa hispida ladogensis) en eau douce et de son nouveau-né durant la saison de reproduction de 2020, lorsque moins de 1 % du lac Ladoga était couvert de glace. Nous avons repéré un nouveau-né dans la zone côtière d’une île et avons suivi son évolution sur la terre ferme à l’aide de la méthode du piège photographique à la lumière du jour. En tout, nous avons pris 2 978 photos, et les phoques étaient présents dans 637 d’entre elles. La femelle a nourri ...